2020
DOI: 10.3892/ol.2020.12387
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic characteristics of 665 patients with myelodysplastic syndrome in China: A single‑center report

Abstract: The karyotype is highly important for diagnosis and prognosis in myelodysplastic syndrome (MDS). The objective of the present study was to investigate the cytogenetic characteristics of patients with MDS in China. The karyotypes of 665 Chinese patients with MDS were analyzed, and it was identified that 298 cases (298/665, 44.8%) had abnormal karyotypes. Among the 298 patients with abnormal karyotypes, the 75 patients with trisomy 8 (+8) constituted the most common subset (75/298, 25.2%). The incidence of abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
5
2
1
Order By: Relevance
“…Our study cohort showed a high frequency (32.6%) of MDS-MLD subgroup (Supplementary Table S1 ) followed by MDS with excess blast (EB1 and EB2) (30.2%) among other MDS subgroups. Our results were similar with the study reported from the Pakistan (26.9%, 22%) 3 , 29 and China (57.6%, 63.6%) 21 , 22 . The studies 3 , 21 , 22 , 29 also reported that the MDS excess blast (EB1 and EB2) was the second most frequent subgroups (32.6%, 39%, 15.3%, and 30%).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study cohort showed a high frequency (32.6%) of MDS-MLD subgroup (Supplementary Table S1 ) followed by MDS with excess blast (EB1 and EB2) (30.2%) among other MDS subgroups. Our results were similar with the study reported from the Pakistan (26.9%, 22%) 3 , 29 and China (57.6%, 63.6%) 21 , 22 . The studies 3 , 21 , 22 , 29 also reported that the MDS excess blast (EB1 and EB2) was the second most frequent subgroups (32.6%, 39%, 15.3%, and 30%).…”
Section: Discussionsupporting
confidence: 93%
“…Our results were similar with the study reported from the Pakistan (26.9%, 22%) 3 , 29 and China (57.6%, 63.6%) 21 , 22 . The studies 3 , 21 , 22 , 29 also reported that the MDS excess blast (EB1 and EB2) was the second most frequent subgroups (32.6%, 39%, 15.3%, and 30%). On the other hand reports from western countries (USA, Switzerland and Netherland) 24 reported MDS-U, more frequent (61%, 60.7% and 42.6%) MDS subgroup and the MDS-EB frequency is found to be less (16.3, 17.5%, 20.2% vs. 32.6%, 39%, 15.3%, 30%) compared with the Asian countries 3 , 21 , 22 , 29 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations